2019
DOI: 10.3390/app9204435
|View full text |Cite
|
Sign up to set email alerts
|

A Steam Ejector Refrigeration System Powered by Engine Combustion Waste Heat: Part 2. Understanding the Nature of the Shock Wave Structure

Abstract: In general, engine fuel combustion generates 30% waste heat, which is disposed to the environment. The use of the steam ejector refrigeration to recycle the waste heat and transfer them to useful energy source could be an environmentally friendly solution to such an issue. The steam ejector is the main component of the ejector refrigeration system, which can operate at a low-temperature range. In this article, the internal shock wave structure of the ejector is comprehensively studied through the computation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…This distance is sometimes presented in its nondimensional form with respect to the throat diameter. This factor has a highly significant effect on the ejector efficiency when the operating conditions are different from the on-design conditions [4][5][6][7]. The existence of at least an optimum NXP that maximizes the ejector performance was stated in different studies (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…This distance is sometimes presented in its nondimensional form with respect to the throat diameter. This factor has a highly significant effect on the ejector efficiency when the operating conditions are different from the on-design conditions [4][5][6][7]. The existence of at least an optimum NXP that maximizes the ejector performance was stated in different studies (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that when the nozzle exit position is fixed, the ejector's COP is positively related to the diameter of the constant section. Han et al studied the internal flow structure [28] and shock waves [29] inside a steam ejector powered by engine combustion waste heat. It was found that the internal flow structure, such as the pseudoshock region and normal shock position, can affect the entrainment ratio.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the aspect of experimental study, the experimental study of the ejector is insufficient. Han et al reported the structure of the internal steam ejector flow [ 18 ] and shock wave [ 19 ] driven rejected combustion engine heat source. The research revealed the potential effect of the internal structure flow on the entrainment ratio (determined as the ratio between the suction and the motive nozzle mass flow rates), mainly the location of the normal shock and the pseudo-shock region.…”
Section: Introductionmentioning
confidence: 99%